Water-to-Fuel Conversion Device via Electrolysis Using Stainless-steel Electrodes - Sholehah, Febriyanti; Haleza, Nur; Syafutra, Muhammad Anggih; Alfernando, Oki; Muis, Lince (Journal of Innovation Process and Environmental Technology, 2025)
Every year, the increase in essential human needs results in an increase in energy use due to population growth and the increasingly rapid development of the technology industry, which has caused almost all sectors to depend on energy and technology. So, the latest and most recent energy is one of the highlights that is very important in the development of science. The water electrolysis method can convert water (H2O) into HHO gas. In the electrolysis of water, various kinds of catalysts are often used, one of which is NaOH, which will be used in this study. The purpose of adding a catalyst is to speed up the reaction rate. So, in this study, the researchers designed an HHO generator to convert H2O into engine fuel using the water electrolysis method, which can produce hydrogen gas. The variables used in this study were variations in the concentration of the NaOH catalyst, namely 5%, 10%, 15%, 20%, and 25%. The electrodes used are stainless steel electrodes with a volume of electrolyte solution equal to 1.5 liters. The number of electrodes is 18 pieces, and the electric current used is 10 Amperes, with the electric voltage being 12 volts. The most optimal tool efficiency is found at the concentration of 25% NaOH solution, which achieves an efficiency of 87.3%.